Study protocol for an investigation of the effectiveness of the pain toolkit for people with low back pain: double-blind randomised controlled trial - Gillian Findley; Cormac Ryan; Amy Cartwright; Denis Martin (BMJ Open)
Introduction The Pain Toolkit is a self-management tool for people with persistent pain. It is available for use worldwide in multiple formats. To date, no studies have investigated the effectiveness of this intervention. This study aims to investigate the effectiveness of the Pain Toolkit in comparison with a simple education control for people with low back pain.Methods and analysis Participants who have been discharged from the North of England Regional Back Pain Pathway will be randomised using sealed, consecutively numbered opaque envelopes to receive either the Pain Toolkit and the Back Book (intervention group) or the Back Book only (control group). Both the therapist and the participant will be blind to group allocation. The primary outcome measure will be disability (Oswestry Disability Index (ODI)). Secondary outcome measures will be pain (0–10 numerical scale), healthcare use (number of healthcare professional visits) and quality of life (EuroQol-5D). Outcome measures will be completed at baseline and at 6 and 12 months. Data will be analysed using analysis of covariance, adjusting for baseline values. A change of 10 points in the ODI will be considered a clinically important change. Additionally, a subsample of participants from the intervention group will undergo semistructured interviews to explore individuals’ experience of the Pain Toolkit. Participants will be asked questions about the ease of use and acceptability of the Pain Toolkit and also for how long they used the Toolkit. The qualitative data will be analysed using thematic analysis.Ethics and dissemination Approval for the study was given by the Health Research Authority and the North East Newcastle, North Tyneside 2 Regional Ethics Committee (reference 18/NE/0144) and Teesside University (reference 176/17). Findings will be disseminated through peer-reviewed journals and presentation at relevant patient groups, and local, national and international conferences.Trial registration number NCT03791164; Pre -results.